2008
DOI: 10.1038/eye.2008.301
|View full text |Cite
|
Sign up to set email alerts
|

The visual and refractive outcomes of combined and sequential penetrating keratoplasty, cataract extraction, and intraocular lens insertion

Abstract: Purpose The aim of this study was to investigate the visual and refractive outcome of combined penetrating keratoplasty, cataract extraction, and intraocular lens insertion (triple procedure) compared with cataract surgery following penetrating keratoplasty (sequential surgery). Methods Retrospective cohort study of 1256 first penetrating keratoplasty for Fuchs' dystrophy performed between April 1999 and December 2005. In all, 1202 triple and 54 sequential procedures were reviewed. At 1 year, refractive outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
1
12
0
1
Order By: Relevance
“…Previous studies have shown that 44 to 64% of the patients develop cataracts within 5 years of penetrating keratoplasty, which is significantly higher than the rate in the general population at the same age [6, 1417]. This higher incidence of cataract formation after PKP can be attributed to intraoperative lens trauma, postoperative inflammation, and topical steroid use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that 44 to 64% of the patients develop cataracts within 5 years of penetrating keratoplasty, which is significantly higher than the rate in the general population at the same age [6, 1417]. This higher incidence of cataract formation after PKP can be attributed to intraoperative lens trauma, postoperative inflammation, and topical steroid use.…”
Section: Discussionmentioning
confidence: 99%
“…This higher incidence of cataract formation after PKP can be attributed to intraoperative lens trauma, postoperative inflammation, and topical steroid use. Cataract developing after keratoplasty can be managed safely using advanced phacoemulsification techniques and IOL implantation, with no increased risk of endothelial cell loss, endothelial graft rejection, or failure [1517]. …”
Section: Discussionmentioning
confidence: 99%
“…Conventional triple procedures have excellent anatomic success in terms of graft clarity and survival but only moderately good functional results. [21][22][23] Nguyen et al 21 evaluated the visual and refractive results in a 1-year follow-up of 499 eyes that had the conventional triple procedure. The authors report that 61% of patients had a postoperative CDVA of 20/40 or better; however, 47% had a refractive error of less than 2.00 D shift from the target refraction of emmetropia.…”
Section: Discussionmentioning
confidence: 99%
“…The significant attrition and uneven group sizes limits the utility of the study, but overall the study suggests that in elderly patients with coexisting cataract and Fuchs' endothelial dystrophy, the triple procedure is advantageous given the similar outcome measures and increased visual recovery from a single surgical experience. 31 Another retrospective study examining similar outcome measures of vision and refraction post-PK versus posttriple in Fuchs' patients was carried out with somewhat longer follow-up. Das et al 32 found that there was no statistically significant difference in visual acuity or refraction between the 2 groups after a mean follow-up of 2.9 years.…”
Section: ' Combined Cornea/cataract or Simply Cataract Surgerymentioning
confidence: 99%